Prognostic Value of Cardiopulmonary Exercise Testing in Heart Failure With Reduced, Midrange, and Preserved Ejection Fraction - Nadruz, Wilson; West, Erin; Sengeløv, Morten; Santos, Mário; Groarke, John D.; Forman, Daniel E.; Claggett, Brian; Skali, Hicham; Shah, Amil M. (Journal of the American Heart Association, 2017)
Background This study aimed to compare the independent and incremental prognostic value of peak oxygen consumption (VO2) and minute ventilation/carbon dioxide production (VE/VCO2) in heart failure (HF) with preserved (HFpEF), midrange (HFmEF), and reduced (HFrEF) ejection fraction (LVEF). Methods and Results In 195 HFpEF (LVEF ≥50%), 144 HFmEF (LVEF 40–49%), and 630 HFrEF (LVEF <40%) patients, we assessed the association of cardiopulmonary exercise testing variables with the composite outcome of death, left ventricular assist device implantation, or heart transplantation (256 events; median follow‐up of 4.2 years), and 2‐year incident HF hospitalization (244 events). In multivariable Cox regression analysis, greater association with outcomes in HFpEF than HFrEF were noted with peak VO2 (HR [95% confidence interval]: 0.76 [0.67–0.87] versus 0.87 [0.83–0.90] for the composite outcome, Pinteraction=0.052; 0.77 [0.69–0.86] versus 0.92 [0.88–0.95], respectively for HF hospitalization, Pinteraction=0.003) and VE/VCO2 slope (1.11 [1.06–1.17] versus 1.04 [1.03–1.06], respectively for the composite outcome, Pinteraction=0.012; 1.10 [1.05–1.15] versus 1.04 [1.03–1.06], respectively for HF hospitalization, Pinteraction=0.019). In HFmEF, peak VO2 and VE/VCO2 slope were associated with the composite outcome (0.79 [0.70–0.90] and 1.12 [1.05–1.19], respectively), while only peak VO2 was related to HF hospitalization (0.81 [0.72–0.92]). In HFpEF and HFrEF, peak VO2 and VE/VCO2 slope provided incremental prognostic value beyond clinical variables based on the C‐statistic, net reclassification improvement, and integrated diagnostic improvement, with models containing both measures demonstrating the greatest incremental value. Conclusions Both peak VO2 and VE/VCO2 slope provided incremental value beyond clinical characteristics and LVEF for predicting outcomes in HFpEF. Cardiopulmonary exercise testing variables provided greater risk discrimination in HFpEF than HFrEF.